Edukasi Keluarga Dalam Perawat ODGJ Dengan Defisit Perawat Diri Di Putri Hijau Provinsi Bengkulu - Wafiqa Azzahrah; Tira rahmawati; Della Dwi Sejati; Debbei Cica Midia; Metriani Metriani; Anes Juni Artika; Ade Herman Surya Direja (Pusat Riset dan Inovasi Nasional, 2024)
Health training close to home is a state of flourishing, where individuals can know their limits, can cope with the pressures of life that afflict one, and work with passion and can contribute to their environment. One of the deep welfare issues that often occurs is the family's ability to supervise People with Mental Disorders (ODGJ), the disgrace that exists in the eyes of the community, such as the use of terms adjacent to ODGJ, clearly affects their anxiety. The pretext of social class against ODGJ also has an impact on the decline of certainty and the destruction of their honor. The purpose of this welfare preparation is to increase family data on the meaning of the family's role in targeting ODGJ. The technique used in this activity is to provide face-to-face preparation in Putri City. The examination was coordinated on October 31, 2023. The output of this activity is the development of family data in handling ODGJ. The end is the expansion of family data on the role of the family in targeting ODGJ at home.